The Influence of the Ability to Read the Quran on Arabic Language Learning Outcomes at Madrasah Tsanawiyah Asy Syifa Balikpapan - Dimas Ramadhan; Iskandar Yusuf (Penerbit Hellow Pustaka, 2025)
This study is designed to examine the impact of the ability to read the Qur'an on the achievement of learning Arabic at Madrasah Tsanawiyah Asy Syifa Balikpapan. With a cooperative quantitative approach, a population of 200 students was studied and 35 students were randomly selected as samples. To collect data, this study used a questionnaire consisting of ten questions using the Likert Scale. Data analysis was carried out by applying reliability tests directly through SPSS 25. The R Square value obtained at 0.590 indicates that there is a significant correlation between the ability to read the Qur'an and the achievement of learning Arabic. This means that the ability to read the Qur'an contributes by 59% to the variation of Arabic learning outcomes. Furthermore, a reliability coefficient of 0.785 indicates that every 1% increase in Qur'anic reading ability will increase Arabic learning achievement by 0.785. In conclusion, the ability to read the Qur'an has a positive impact on Arabic learning outcomes, so it is very important to integrate the teaching of reading the Qur'an into the Arabic curriculum in madrassas to improve student achievement.